Anthraquinones and their analogues as potential biocontrol agents of rust and powdery mildew diseases of field crops. Issue 8 (10th June 2022) - Barilli, Eleonora; Agudo, Francisco J.; Masi, Marco; Nocera, Paola; Evidente, Antonio; Rubiales, Diego
Abstract: Background: Rusts and powdery mildews are severe fungal diseases of major crops worldwide, including cereals and legumes. They can be managed by chemical fungicide treatments, with negative consequences as environmental pollution and risk for human and animal health. Bioactive natural products could be the safest alternative for pest control. The family of anthraquinones, as well as analogue compounds containing an anthraquinone moiety or some modified anthraquinone rings, has been reported to exhibit certain antibiotic activity. Thus, the potential antifungal activity of some anthraquinones isolated from Ascochyta lentis, was assayed in this study for their effectiveness to reduce rust and powdery mildew diseases on pea and oat. Their effect on fungal development was macro‐ and microscopically assessed on inoculated leaves, and compared to the control achieved by the chemical fungicide (Tetraconazol 12.5% and Azoxystrobin 25%). In addition, the most promising compound was also tested at different concentrations in inoculated whole plants in order to evaluate its preventive and curative potential against fungal infection. Results: All metabolites studied strongly reduced the development of rust and powdery mildews in both pea and oat, being pachybasin and lentiquinone C the most effective ones in hampering fungal spore germination and appressoria formation. Some of them also affected post‐penetration events reducing colony size and number of haustoria per colony. Results were confirmed for pachybasin in whole plants assays, showing an efficacy similar to the commercial fungicide to control fungal diseases, both in preventive and curative applications. Conclusions: Some fungal anthraquinones and close metabolites, especially pachybasin, could be very promising molecules with effective potential as antifungal agents against both rust and powdery mildew of both pea and oat. Some structure activity‐relationships feature have also been evaluated. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Biotrophic fungi as rust and powdery mildew can cause severe physiological damage in crops of agronomic importance. This article highlights the importance of some fungal anthraquinones and their analogues, especially pachybasin, which are very promising molecules with effective potential as safely biofungicide.